ON BEING A CLIENT - St John, A. (Social Work/Maatskaplike Werk, 2003)
Last month a social worker whom I had never met, and with whom I was having my first contact as a client (per telephone) said to me, as an opening statement, “Well, first of all I need to tell you that I think you are crazy!”